The Influence of Organizational Culture on Organizational Commitment and Job Satisfaction and Its Impact on Employee Performance - Yusuf Harianto; Muhammad Asdar; Syamsu Alam (Magister Management, Hasanuddin University, 2020)
This study aims to determine the influence of an organizational culture that has been applied to the Regional Civil Service Agency and Human Resources Development of Boven Digoel Regency on organizational commitment and job satisfaction. In addition, this study also aims to see the indirect effect of organizational culture on employee performance when mediated by organizational commitment and job satisfaction. This research is a quantitative study using a questionnaire to collect data and then processed using Smart PLS software with the path analysis method. The results of the study found that organizational culture has a positive and significant effect on organizational commitment and job satisfaction. Furthermore, the effect of organizational commitment and job satisfaction partially does not have a significant effect on employee performance. As for the indirect effect, it shows that organizational commitment and job satisfaction cannot significantly mediate the influence of organizational culture on employee performance.re on employee performance.